Effect of oxidation temperature on surface oxide film structure and corrosion resistance of 50 steel - Guilin Liu; Bo Liang; Zhimin Ding (Heliyon)
The phase structure, thickness and corrosion resistance of oxidation film of 50 steel oxidized at 200∼600 °C in an air furnace were studied by AES, SEM, XRD and EIS in this paper. The results show that the concentration of surface oxygen atoms of 50 steel shows a trend of rapidly increasing to a peak, maintaining stability for a distance, then decreasing, and finally stabilizing after oxidation treatment at different temperatures. The peak concentration of oxygen atoms and the stabilization distance are found to vary with the oxidation temperature. The oxidation activation energy is 25.2 kJ/mol. With the increase of oxidation temperature, the oxide film composed of the outer Fe2O3 layer and the inner Fe3O4 layer is generated on the surface of 50 steel, and Fe2O3 is the primary constituent. Moreover, the corrosion of oxide film in NaCl solution is marked by anodic activation dissolution. The thermal oxidation samples demonstrate better corrosion resistance than the original samples with the increase of oxidation temperature, there is an upward trend in the self-corrosion potential, whereas a decreasing trend in the corrosion current density, and the capacitor-reactance arc radius is gradually increased. The maximum corrosion potential, the minimum corrosion current density and the largest capacitor-reactance arc radius are recorded at 600 °C, at which temperature it has the best corrosion resistance.